DUKUNGAN SOSIAL DARI SUPERVISOR DAN REKAN KERJA DALAM KONTEKS KERJA JARAK JAUH: TINJAUAN CAKUPAN SISTEMATIS - Yogatama, Ahmad Nizar (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2025)
This scoping review aims to comprehensively map and analyze existing literature on the roles of supervisor and coworker support in remote and hybrid work contexts. The review systematically examined studies published between 2015 and 2025 across multiple databases. Findings reveal that both supervisor and coworker support significantly enhance psychological well-being and work engagement while mitigating strain and burnout. Supervisor support primarily contributes to role clarity and work–life balance, whereas coworker support strengthens social connectedness and collaboration. When combined, these supports generate synergistic benefits, amplifying positive outcomes for employees and organizations